The first steps into physiotherapy: A qualitative exploration of student motivations and early-career intentions as they prepare to enter the workforce - Jones, Abraham HKW; Dinsdale, Alana; Mandrusiak, Allison; Forbes, Roma (Physiotherapy theory and practice, 2025)
New graduate physiotherapists play a vital role in meeting the increased demand for health services, and aligning graduate career aspirations with evolving workforce needs is crucial for the profession's future. However, little is known about the underlying motivating factors that influence early-career intentions for physiotherapy students preparing to enter the workforce. To explore the motivating factors influencing physiotherapy students preparing to enter the workforce and the impact of these factors on workplace and early-career intentions. Semi-structured interviews were conducted with Australian entry-level physiotherapy students in their final six months of study ( = 13), recruited through a snowball sampling approach. Data were analyzed using reflexive thematic analysis. The Self Determination Theory was used to guide the interview framework, inform data analysis, and interpret participants' deeper motivations. Four major themes were developed and structured as statements made from the perspectives of participants: 1) I want my personal values to be fulfilled; 2) Supports I seek in my professional setting; 3) Relationships I hope to form within my career; and 4) Experiences that shape my early-career intentions. The findings indicate that physiotherapy students are influenced by a combination of intrinsic and extrinsic motivations, alongside their placement experiences, when making decisions at the outset of their career. Consistent with Self Determination Theory, students seek to fulfill their innate psychological needs of competence, autonomy, and relatedness, and recognize the importance of aligning their values with prospective team environments and people in their early career.